2009
DOI: 10.1108/14684520910951249
|View full text |Cite
|
Sign up to set email alerts
|

The effective use of technology in personal knowledge management

Abstract: Purpose -The objective of this paper is to further explore the emerging concept of personal knowledge management (PKM) and to bring researchers' attention to this notion. Specifically, this paper aims to address issues related to the effective utilisation of technology in PKM practices. Design/methodology/approach -A theoretical framework incorporating PKM skills, technology tools, user context and skills-tools fit is proposed. Arguments are built on the task-technology fit theory, which explores the link betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 23 publications
0
42
0
3
Order By: Relevance
“…Empirical investigations have shown that knowledge workers often spend a substantial amount of work time tracking lost documents; in the worst cases they have to rewrite them (Agnihotri and Troutt 2009). On the other hand, there are many opportunities to tackle problems such as these by enhancing the level of information ergonomics.…”
Section: Information Ergonomics As a Novel Approach To Information Lomentioning
confidence: 98%
“…Empirical investigations have shown that knowledge workers often spend a substantial amount of work time tracking lost documents; in the worst cases they have to rewrite them (Agnihotri and Troutt 2009). On the other hand, there are many opportunities to tackle problems such as these by enhancing the level of information ergonomics.…”
Section: Information Ergonomics As a Novel Approach To Information Lomentioning
confidence: 98%
“…Kumpulan dari keterampilan tersebut, dirangkum Dorsey (2000) dalam Agnihotri & Troutt (2008) ke dalam tujuh keterampilan PKM (PKM Skills), yaitu: (1) pengambilan informasimerupakan keterampilan yang digunakan untuk mengelola proses pencarian individu (contoh: pelebaran atau penyimpatan pencarian), Boolean logic dan aplikasi pengulangan pencarian; (2) pengevaluasian informasi. Dengan tujuan untuk menemukan informasi yang berharga dan relevan, maka PKM mengehendaki evaluasi dari informasi yang tersedia secara luas, yang tidak disaring ataupun disensor; (3) pengaturan informasi -pengaturan dari informasi (contoh: kronologikal, fungsional, role-based) memfasilitas KM dengan cara menghubungkan informasi baru dan lama; (3) analisis informasi -membangun keterampilan organisasi informasi dalam menganalisis dapat membantu pengguna untuk mengubah informasi menjadi pengetahuan; (4) penyajian informasiketerampilan PKM melibatkan penyajian informasi kepada pihak lain, melalui desain yang efektif dan komunikasi; (5) pengamanan informasi -dengan adanya pertumbuhan resiko dan kesempatan yang terasosiasi dengan information sharing, para knowledge worker harus dapat menjamin keamanannya; (6) pengkolaborasian di sekitar informasi -keterampilan PKM yang memungkinkan para knowledge worker untuk berpartisipasi dalam aktifitas yang bernilai tinggi (high-value activities) di dalam suatu proses kolaborasi di sekitar informasi.…”
Section: Personal Knowledge Management (Pkm)unclassified
“…Oleh karena itu, tools dari PKM harus sejajar dengan keahlian khusus serta PKM yang dipilihnya. Hal ini untuk membantu para pengguna dalam melakukan berbagai knowledge activites (Agnihotri & Troutt, 2008). Berdasarkan survei yang dilakukan oleh Razmerita et al (2008) terhadap tools Web 2.0 yang ada saat ini, tools PKM dapat dibagi menjadi enam kategori sebagai berikut:…”
Section: Personal Knowledge Management Tools Dalam Social Webunclassified
“…As reviewed by Raj Agnihotri and Marvin D. Troutt (2009), an electronic PKM system should enhance our innate PKM's ability to retrieve, evaluate, organize, analyze, present, secure, and collaborate around information. Current capabilities that might be incorporated into a PKM include index/search, metasearch, link association, information capturing and sharing, concept/mind mapping, e-mail management, analysis and unified messaging, voice recognition, collaboration and synchronization, and other learning tools (Agnihotri and Troutt 2009). In practice, librarians usually use several of these tools to manage their knowledge of resources as illustrated in Figure 2.…”
Section: The Advantages Of Using Xml To Build Your Pkm System Comparementioning
confidence: 99%